2003
DOI: 10.2520/myco.53.11
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of pyranone and furanone derivatives, isolated from Aspergillus sp. IFM51759, against Aspergillus fumigatus

Abstract: The incidence of life-threatening fungal infections has steadily increased in immunocompromised hosts such as HIV infected persons and cancer patients. 1) Invasive pulmonary aspergillosis and Pneumocystis carinii pneumonia are a leading cause of deaths in bone marrow transplant recipients and in HIV-infected patients, respectively. Moreover, resistance to the azoles which are the most widely used antifungals today is attracting much attention. Therefore, new antifungal agents are continuously required to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Based on the detailed 1 H, 13 C NMR and 2D NMR, COSY and HMBC spectra, compound (6) was identified as (Argoudelis and Zieserl, 1966;Yang et al, 1997;Komai et al, 2003), and compound (7) as (+)-(6R, 7S)-dia-asperlin, which was originally reported from Aspergillus caespitosus (Mizuba et al, 1975;Yang et al, 1997). This structure was confirmed by a synthetic method (Murayama et al, 1987).…”
Section: Extraction Purification and Identification Of Phytotoxinsmentioning
confidence: 76%
“…Based on the detailed 1 H, 13 C NMR and 2D NMR, COSY and HMBC spectra, compound (6) was identified as (Argoudelis and Zieserl, 1966;Yang et al, 1997;Komai et al, 2003), and compound (7) as (+)-(6R, 7S)-dia-asperlin, which was originally reported from Aspergillus caespitosus (Mizuba et al, 1975;Yang et al, 1997). This structure was confirmed by a synthetic method (Murayama et al, 1987).…”
Section: Extraction Purification and Identification Of Phytotoxinsmentioning
confidence: 76%
“…Since eushearilide (1) was insoluble in water, the antimicrobial activity was determined by the paper disc method, as described in the previous paper [2,3]. The results are summarized in Table 1.…”
Section: Antimicrobial Propertymentioning
confidence: 99%
“…It has been isolated previously from several species of the fungal genera Nigrospora (Fukushima et al 1998;Trisuwan et al 2009;Wu et al2009), Xylaria (Jimenéz-Romero et al 2008, Aspergillus (Komai et al 2003), Verticillium (Khambay et al 2000), Drechslera (Krivobok et al 1994), Hirsutella (entomopathogenic) ( K r a s n o f f a n d G u p t a 1 9 9 4 ) , P a e c i l o m y c e s (entomopathogenic) (Wu et al 2012), and Phoma (Yamamoto et al 1970). Phomolactone has antifungal activity against Aspergillus fumigatus (Komai et al 2003), nematocidal activity (Khambay et al 2000), immunomodulating activity (Krivobok et al 1994), insecticide activity (Krasnoff and Gupta 1994), phytotoxic activity (Fukushima et al 1998), and weak activity against Plasmodium falciparum (Jimenéz-Romero et al 2008). Its ecological role(s) in each of these species has not been rigorously studied, but its phytotoxic, fungitoxic, and insecticidal activities may be important to the various fungi that produce phomalactone.…”
Section: Resultsmentioning
confidence: 99%